Pengaruh Model Pembelajaran Problem Based Learning Berbantuan Media Kartu Bergambar Sederhana Terhadap Hasil Belajar Siswa Pada Materi Perkalian Bilangan Asli Di Kelas II SD Inpres Nunbaun Delha - Dera Halakadu, Maria Felisiani; Nenohai, Juliana M. H.; Vera Rosalina Bulu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Research with the title "The Influence of the Problem Based Learning Model Assisted by Simple Picture Card Media on Student Learning Outcomes on Multiplication of Natural Numbers in Class II SD Inpres Nunbaun Delha." The aim is to determine the effect of the Problem Based Learning (PBL) learning model assisted by simple picture card media on student learning outcomes in the mathematics subject of multiplying natural numbers for class II SD Inpres Nunbaun Delha. The type of research used is quantitative research. The population in this study was class II students at SD Inpres Nunbaun Delha 2025/2026, totaling 52 people. The sample used in this research was divided into 2 classes with a total of 27 people in class II A and 25 people in class II B. The data collection technique used was a test using 20 multiple choice questions. The data analysis techniques used are normality tests, homogeneity tests and hypothesis tests. The results of this research show that in the normality test the posttest score for the experimental class had a significant value of 0.019 and was declared to be abnormally distributed, and the posttest score for the control class had a significant value of 0.354 which was declared to be normally distributed. In hypothesis testing using the Mann-Whitney U Test on the posttest scores of the experimental class and the control class Asysmp scores. Sig. (2-tailed) namely 0.001 which shows that there is a significant difference in the learning outcomes of students who are taught using the PBL model. The final Mathematics learning results in the experimental class were 88% and in the control class 26% of students completed. Based on the research results above, it can be concluded that the application of the Problem Based Learning (PBL) model has a significant influence on the learning outcomes of class II students compared to conventional learning